Welfare states achievements and threats - Lindert, Peter H. 1940- (Cambridge University Press, 2019)
The traditionally, and wrongly, imagined vulnerabilities of the welfare state are economic. The true threats are demographic and political. The most frequently imagined threat is that the welfare state package reduces the level and growth of GDP. It does not, according to broad historical patterns and non-experimental panel econometrics. Large-budget welfare states achieve a host of social improvements without any clear loss of GDP. This Element elaborates on how this "free lunch" is gained in practice. Other threats to the welfare state are more real, however. One is the rise of anti-immigrant backlash. If combined with heavy refugee inflows, this could destroy future public support for universalist welfare state programs, even though they seem to remain economically sound. The other is that population aging poses a serious problem for financing old age. Pension deficits threaten to crowd out more productive social spending. Only a few countries have faced this issue well
Keywords: Bevölkerungsentwicklung; Wohlfahrtstheorie; Welfare state